Breeding and lactation efficiencies and lifetime productivity of Jaffrabadi buffaloes - P.U. GAJBHIYE, M.R. GADARIYA, P.H. VATALIYA K.S. MURTHY, H.H. SAVSANI (Indian Journal of Animal Production and Management, 2019)
Breeding efficiency and lactation efficiency during the productive herd-life along with lifetime productivity based on 863 calving of 149 Jaffrabadi buffaloes calved and performed during 1991 to 2010 at Cattle Breeding Farm, JAU, Junagadh were studied. Productive life, lifetime total milk production (LTMP) and maximum standard lactation Yield (MSLMY) and association of breeding and lactation efficiencies with production traits were also investigated. The age at first calving (AFC) and over-all calving interval (CI) of Jaffrabadi buffaloes were, 1656.68±28.57 days (54.3months) and 541.94±7.88 days (17.8 months), respectively. Calving interval ranged between from 532 to 558 among different lactations, the parity effect being non-significant. In general, it increased from 1st to 4th lactation. Then after the trend was not definite. The breeding efficiency as per Wilcox (BE-W) of the Jaffrabadi buffaloes based on all calvings during life time averaged 74.69±2.47%. When AFC was also taken into account, breeding efficiency of the buffaloes as per Tomar (BE-T) was estimated to be 79.04±1.46 %. About 28 % of heifers calved for the first time below the average age of 47 months and 31 % of buffaloes calved at an average calving interval of 15 months. Lactation period of Jaffrabadi buffaloes varied from 247.50 to 335.69 days, over-all average being 291.87±4.96 days. The parity effect was significant (p<0.05) with no definite trend. Overall lactation efficiency (L.E.) defined as lactation days/calving Interval × 100 of the Jaffrabadi buffaloes was 58.19±1.61%. Total lactation milk yield (TLMY) and standard lactation milk yield (SLMY) of Jaffrabadi buffaloes averaged 1800.46±32.21 and 1681.64±23.73litres, respectively. Parity number significantly (p<0.05) affected these production traits. Milk production of the buffaloes increased with increase in number of parity, reaching peak TLMY (2130 litres.) and SLMY (1890 litres) in 4th lactation. Then-after, although their productivity decreased marginally, TLMY was 1900-2000 litres, SLMY being 1700-1800 liters up to 6th lactation. Productive life defined as AFC plus number of days in all calving averaged 3701.12±135.95 days (10.14 years). Mean number of calving during lifetime was 4.74 ±0.22. About 20 % Jaffrabadi buffaloes remained in the herd for more than 12 years of age (on an average 16.6 years) and more than 38 % of these animals performed in the herd for more than 6 lactations. Jaffrabadi herd registered 8450.80±593.40 litres. LTMP with 2154.12±74.13 litres as average MSLMY. BE-T and LE of the buffaloes were positively but lowly associated with LTMP (r-value, 0.16) and with MSLMY (r-value, 0.21 to 0.25). The association of AFC was significant with BE-T (r value, 0.25) only. The 1st CI and 2nd CI with BE-W and BE-T both and C2 with BE-T showed a correlation (r= 0.59 to 0.67, p<0.01) of high magnitude. The 1st LP only was lowly correlated (r-value, 0.15) with LE. Association of LE with BE-W (r = 0.68) and BE-T (r= 0.45) were significant (p<0.01) and medium in magnitude.